A comprehensive study of prophage islands in Burkholderia pseudomallei complex - Khrongsee, Pacharapong; Irby, Iris; Akaphan, Pitchaporn; Alami-Rose, Mariam A.; Kaewrakmuk, Jedsada; Tuanyok, Apichai (Frontiers in Bacteriology, 2024)
Introduction Bacteriophages are known as predators of bacteria and key biological factors influencing genetic recombination through phage transduction in bacteria. Phage transduction is known as one of the most common genetic recombination events found in Burkholderia pseudomallei, a diverse bacterial species and the causative agent of a deadly tropical disease melioidosis. The main objective of this study was to catalog prophages or prophage islands that are common in B. pseudomallei genomes. Methods Various bioinformatic tools were used to identify prophages in 106 complete B. pseudomallei genomes, and complete and incomplete genomes in other species within the B. pseudomallei Complex (BPC). Temperate phages were spontaneously induced from selected B. pseudomallei and B. thailandensis strains, and further characterized by transmission electron microscopy and whole genome sequencing. Results Nine phage integration hotspots were identified in B. pseudomallei pan-genomes, eight of which were associated with tRNA gene-mediated site-specific recombination (tRNA-SSR) events. These genetic events occurred at various tRNA-genes including tRNA- Phenylalanine (anticodon GAA), - Methionine (CAU), - Proline (UGG), - Arginine (UCU), - Cysteine (GCA), - Arginine (CCG), - Serine (GGA), and – Selenocysteine (UCA) genes. Some of these events were also found in other related species within the B. pseudomallei Complex (BPC). We have demonstrated that lysogenic phages from select BPC strains could use B. pseudomallei strain Bp82 or 576mn as a host. These phages were classified into one of the two major groups, myoviruses or siphoviruses, based on their morphology and genomic composition. Discussion We have demonstrated that most B. pseudomallei strains are lysogenic, many containing at least one functional prophage in their genomes. Further investigation of the interactions between B. pseudomallei, bacteriophages, and other environmental and biological factors would provide a bigger picture of genomic diversity, potentially influence on survival of B. pseudomallei in the environment and its pathogenic specialization in hosts.